An antifungal tetrapeptide from the culture of Penicillium canescens - Bertinetti, Brenda Veronica (2009)
A new tetrapeptide D-Phe-L-Val-D-Val-L-Tyr (1), along with three known diketopiperazines and pseurotin A, were isolated from the culture of Penicillium canescens, collected from pollen from beehives, in a screening for new antimicrobial products from unexplored sources. The structure of the tetrapeptide, which exhibits antifungal activity comparable with that of the commercial product benomyl against the soybean phytopathogen Fusarium virguliforme, was determined by spectroscopic (2D-NMR, and MS and MS/MS) and chemical methods, and the sequence was confirmed by comparison with authentic synthetic isomeric peptides. © 2009 Verlag Helvetica Chimica Acta AG.